2003
DOI: 10.1046/j.1365-2648.2003.02580.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing doctor‐ and nurse‐led care in a sexual health clinic: patient satisfaction questionnaire

Abstract: The rigorous development, piloting and testing phases of this satisfaction questionnaire led to reliable and valid results. This study demonstrated that nurse-led clinics within this service are an acceptable alternative to the existing doctor-led clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…13 Evaluations of nurse-led GUM care in the United Kingdom report high client satisfaction and that nurses provide the same standard and level of care as their medical colleagues. [12][13][14] A survey of GUM clinics found that nurses staffed 35% of designated sexual dysfunction clinics. 15 In the researcher's practice setting, the prevalence of female sexual dysfunction combined with its detrimental impact on well-being and relationships highlighted the need for an effective model of health care which addressed the problem.…”
Section: Introductionmentioning
confidence: 99%
“…13 Evaluations of nurse-led GUM care in the United Kingdom report high client satisfaction and that nurses provide the same standard and level of care as their medical colleagues. [12][13][14] A survey of GUM clinics found that nurses staffed 35% of designated sexual dysfunction clinics. 15 In the researcher's practice setting, the prevalence of female sexual dysfunction combined with its detrimental impact on well-being and relationships highlighted the need for an effective model of health care which addressed the problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, the positive effects on patient satisfaction using nurse practitioners in primary care, genitourinary clinics, and emergency departments have not been confirmed in outpatient hysteroscopy clinics [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A validation process was described in five studies,5 8 11 14 15 with three of these adapting pre-existing questionnaires, but no study used a comprehensive approach to questionnaire design incorporating patient input, and an assessment of validity, acceptability, feasibility and reliability.…”
Section: Resultsmentioning
confidence: 99%
“…Pilots were described in only four studies 8 11 14 15. The national NHS outpatient survey is widely used, but it has not been validated in a STI clinic population 32.…”
Section: Discussionmentioning
confidence: 99%